A Summer School for Structuring the Chemoinformatics Community. Issue 6 (June 2014) - Rognan, Didier; Varnek, Alexandre
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>